Carecas do Subúrbio: a experiência urbana narrada pela música, as práticas sociais e a construção de um herói nacional - Matias, Renata Cristina (2018)
This paper analyzes lyrics of the Carecas do Subúrbio urban group bands. However, in knowing the history of the skinheads in Britain, the propagators of ideology, the emergence of the Carecas do Subúrbio movement and the various branches that have emerged over the years to may, thus, profiling of individuals who are part of the group. It was noted, through interviews with members of the group, the relevance of the musical bands for this movement and, also, the significate which them attribute to such terms used on your lyrics. This research, of a qualitative character, elected the bands Hysteria Oi!, Oi!perária Class and Soldados da Pátria, as well as members of the Carecas do Subúrbio movement resident in the São Paulo city (SP), to conduct the case of study. Methodological procedures were used the bibliographic review, the experience of the researcher with the group and field research, in which questionnaires were applied with open questions and, subsequently, conducting of a focal group. The lyrics of musical bands of the group were analyzed and the theme nationalism was verified as the most covered by bands, therefore, analyzed in this study. It has been found that the musical bands are more emblematically in field of social conflict and that they are the propagators of the Carecas do Subúrbio ideology. It turned out that the members of the group believe that their ideology, that values by nationalism and the traditionalism, is ideal for the country. The Carecas believe that they are the soldiers of the homeland and that, with their ideology, will achieve a better Brazil for everyone. They believe to be the national heroes and that the violence established in the group is justified, once they fighting for the ideology that will save the brazilians of the problems in sectors as education, health and economy